Factors Affecting Knowledge Transfer: A Systematic Literature Review and the Method to Assess Manufacturing Company’s Readiness for Knowledge Transfer Projects - Dubickis Mikus; Zarina Agnese; Putans Romans (Economics and Culture)
In today’s business environment, with organizations enhancing performance, maintaining a competitive edge, and fostering innovation, the efficient transfer of knowledge plays an increasingly pivotal role. As industries recognize the importance of and strive for more and more productive knowledge transfer, understanding the factors affecting this process becomes imperative. Manufacturing is considered a strategic sector, and well-performing knowledge transfer is necessary for higher innovation and competitiveness. To increase knowledge transfer performance, companies must have the awareness, ability, and opportunity to identify the main aspects that need operational improvement. Studies based on systematic literature review and mapping impact factors have shown that knowledge transfer is hypothetically affected by a vast variety of factors, which creates challenges for companies in selecting and applying these factors. Therefore, the two research questions of this study are – RQ1: What are the relationships between the knowledge transfer-influencing factors identified in the literature analysis and the dependent variables? RQ2: What is the weight of the statistically significant factors identified in the empirical study?